The Basilan attack: first significant IS battle in Southeast Asia - Gunaratna, Rohan (2016)
Following the attack by IS on the Philippine army in Western Mindanao, Manila should make fighting IS its national security priority and step up cooperation with its counterparts in Southeast Asia to eliminate the threat. Otherwise, IS will grow and affect the security and stability of the region.